The Potential of Food Protein-Derived Bioactive Peptides against Chronic Intestinal Inflammation - Wanying Zhu; Liying Ren; Li Zhang; Qinqin Qiao; Muhammad Zahid Farooq; Qingbiao Xu (Hindawi Limited, 2020)
Inflammation can cause various chronic diseases like inflammatory bowel diseases. Various food protein-derived bioactive peptides (BAPs) with anti-inflammatory activity have the potential to manage these diseases. The aim of this paper is to overview the mechanisms and the molecular targets of BAPs to exert anti-inflammatory activity. In this review, the in vitro and in vivo effects of BAPs on intestinal inflammation are highlighted. The mechanism, pathways, and future perspectives of BAPs as the potential sources of therapeutic treatments to alleviate intestinal inflammation are provided, including nuclear factor-κB, mitogen-activated protein kinase, Janus kinase-signal transducer and activator of transcription, and peptide transporter 1 (PepT1), finding that PepT1 and gut microbiota are the promising targets for BAPs to alleviate the intestinal inflammation. This review provides a comprehensive understanding of the role of dietary BAPs in attenuating inflammation and gives a novel direction in nutraceuticals for people or animals with intestinal inflammation.